2016
DOI: 10.1371/journal.pone.0168265
|View full text |Cite
|
Sign up to set email alerts
|

The PNPLA3 Genetic Variant rs738409 Influences the Progression to Cirrhosis in HIV/Hepatitis C Virus Coinfected Patients

Abstract: Contradictory data about the impact of the rs738409 steatosis-related polymorphism within PNPLA3 gene on liver fibrosis progression in HIV/hepatitis C virus (HIV/HCV)-coinfected patients have been reported. Our objective was to test whether this, and other polymorphisms previously related to fatty liver disease in HIV infection linked to SAMM50 or LPPR4 genes, influence liver fibrosis progression in HIV/HCV-coinfected individuals. Three hundred and thirty two HIV/HCV-coinfected patients who consecutively atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…15 Furthermore, we did not find any association with advanced fibrosis/cirrhosis which has been noted in other studies. 16 Our findings are in agreement with Scheiner et al, who reported no association between PNPLA3 polymorphisms and fibrosis stage. Similarly, they also reported no clear link between PNPLA3 and effect on virologic response following pegylated interferon/ribavirin therapy.…”
Section: Discussionsupporting
confidence: 93%
“…15 Furthermore, we did not find any association with advanced fibrosis/cirrhosis which has been noted in other studies. 16 Our findings are in agreement with Scheiner et al, who reported no association between PNPLA3 polymorphisms and fibrosis stage. Similarly, they also reported no clear link between PNPLA3 and effect on virologic response following pegylated interferon/ribavirin therapy.…”
Section: Discussionsupporting
confidence: 93%
“…More than fifty studies demonstrating that the PNPLA3 rs738409 G allele is a risk factor for non-alcoholic steatohepatitis (NASH), liver cirrhosis in NASH or alcoholic liver disease have been published in the past decade [511]. The same allele was also identified as a risk factor for liver fibrosis and cirrhosis in HCV-monoinfected individuals [1216] and in those with HCV/HIV coinfection [1720] and it also turned out to be a predisposing factor of hepatocellular carcinoma (HCC) [2124]. In a recent study, the increased risk of HCC and PNPLA3 G allele was found only in alcoholic liver disease, but not in non-alcoholic fatty liver disease or viral hepatitis B and C [25].…”
Section: Introductionmentioning
confidence: 99%
“… 75 In particular, a recent study conducted in a larger population clearly defined the role of I148M PNPLA3 as an independent risk factor for fibrosis progression, resulting in higher cirrhosis occurrence in HIV/HCV co-infected patients. 76 Molecular data have shown that HCV alters dramatically lipid metabolism in infected hepatocytes, 77 suggesting a possible link between I48M PNPLA3 in remodeling LDs and thus favoring fat accumulation leading to steatosis. However, further mechanistic studies are needed to verify this hypothesis.…”
Section: Introduction On Pnpla3: Origin and Tissue-specific Expressiomentioning
confidence: 99%